Piezoelectric self-Fenton composite film and preparation method and application thereof
By adding Fe3O4, MgO and rGO to the piezoelectric material, composite films are prepared to improve catalytic activity, and the problems of high cost of organic dye pollutants treatment and pH limit in the prior art are solved, efficient degradation and catalyst recovery are achieved, suitable for Treatment of organic pollutants in various environments.
Patent Information
- Application Number
- CN202411427684.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The prior art is costly and limited by the environmental pH when treating water-soluble organic dye pollutants, and the catalytic activity of piezoelectric materials is insufficient, making it difficult to effectively degrade organic pollutants.
The heterogeneous Fenton material Fe3O4 is blended with MgO and rGO as filler, and is uniformly dispersed in the piezoelectric material PVDF to prepare a composite film. Through mechanical force, the separation and reaction of electron-hole pairs are promoted to generate reactive oxygen species, and organic pollutants are realized. efficient degradation and simplify catalyst recovery.
It achieves an efficient organic pollutant degradation rate (50-90% or more within 30 minutes), reduces the degradation cost, has wide application and excellent load characteristics, and avoids the limitations of traditional Fenton processes.
Smart Images

Figure CN119306979A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic pollutant treatment, and in particular to a piezoelectric self-Fenton composite film and a preparation method and application thereof. Background Art
[0002] Due to the growth of the world's population and the rapid development of industry, the demand for environmental protection is increasing. Water-soluble organic dye pollutants are highly stable and particularly difficult to handle, which can cause serious health and environmental problems. In order to solve this serious problem, it is urgent to develop environmentally friendly, convenient and inexpensive technologies for degrading organic pollutants.
[0003] At present, the Fenton process (one of the advanced oxidation processes (AOPs)) is widely used to degrade and remove organic dye pollutants. This process mainly uses Fe 2+ Catalyzing H2O2 to generate ·OH with a higher redox potential to achieve catalytic oxidation has a good removal effect, but there are problems such as high treatment cost and environmental pH limitation. Based on the above problems, the researchers discovered a piezoelectric material through research. Its microstructure has non-centrosymmetry, which can achieve the separation of electron-hole pairs under the action of mechanical force, and further react with O2 and H2O in the environment to generate reactive oxygen species (ROS), including ·OH, ·O2 - , 1 O2 and H2O2, etc., have achieved the effect of degrading organic dye pollutants, but the piezoelectric catalytic activity of the piezoelectric materials currently developed is far from satisfactory. Summary of the invention
[0004] The purpose of the present invention is to provide a piezoelectric self-Fenton composite film and its preparation method and application to solve the problems existing in the above-mentioned prior art. The present invention mixes the heterogeneous Fenton material Fe3O4 with MgO and rGO as fillers and evenly disperses them in the piezoelectric material PVDF to prepare a composite film, thereby achieving effective degradation of organic pollutants and efficient recovery of catalysts.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention: a method for preparing a piezoelectric self-Fenton composite film, comprising the following steps:
[0007] Add PVDF into an organic solvent and dissolve it to obtain a polymer solution;
[0008] MgO and rGO are added into an organic solvent for cell crushing, and then the polymer solution is added and mixed evenly to obtain a mixed solution;
[0009] After the mixed solution is spread flat, deionized water is sprayed on the surface to obtain the piezoelectric self-Fenton composite film.
[0010] Furthermore, the method for preparing the piezoelectric self-Fenton composite film also includes adding iron while adding MgO and rGO.
[0011] Furthermore, the iron includes Fe, Fe2O3, Fe3O4, FeS2, FePO4, FeC2O4 or FePc.
[0012] Furthermore, the PVDF includes PVDF-HFP; the amount of iron, MgO and rGO is 3% of the mass of the piezoelectric self-Fenton composite film.
[0013] Furthermore, the cell pulverization treatment is an ultrasonic pulverization treatment; the power of the ultrasonic pulverization treatment is 97.5W, the total time is 25min, and the ultrasonic mode is on for 1.5s and off for 2s.
[0014] The second technical solution of the present invention: a piezoelectric self-Fenton composite film prepared by the above preparation method.
[0015] The third technical solution of the present invention: an application of the above-mentioned piezoelectric self-Fenton composite film in the degradation of organic pollutants.
[0016] Furthermore, the organic pollutants include one or more of rhodamine B (RhB), methylene blue (MB) and methyl orange (MO).
[0017] The fourth technical solution of the present invention: a method for piezoelectric self-Fenton degradation of organic pollutants, comprising the following steps: immersing the above-mentioned piezoelectric self-Fenton composite film in a solution of organic pollutants, and performing a piezoelectric self-Fenton degradation reaction under ultrasound after dark adsorption.
[0018] Piezoelectric self-Fenton degradation mechanism of organic pollutants:
[0019] The abundant mechanical energy in the environment acts on the piezoelectric material, causing it to deform. The dipole moment generated by the non-centrosymmetric structure in the material's microstructure will be reflected as a piezoelectric field on a macroscopic level. The piezoelectric field, as a driving force, promotes the generation of ROS, and the Fenton material can further catalyze H2O2 to produce more high-energy free radicals. In this process, rGO acts as a high-speed transmission channel for separating carriers, promoting the effective separation of electron-hole pairs. MgO provides more abundant active sites for the composite film to improve the degradation efficiency of organic pollutants.
[0020] The present invention discloses the following technical effects:
[0021] (1) The piezoelectric self-Fenton composite film prepared by the present invention has a high pollutant degradation rate: the material can achieve a degradation rate of 50-90% or more for a variety of pollutants within 30 minutes;
[0022] High catalyst recovery efficiency: The material can be easily and conveniently recycled, effectively reducing the degradation cost;
[0023] Excellent load characteristics: The material can be loaded on the surface of objects of various complex shapes to achieve mechanical energy utilization in various environments;
[0024] Wide application: This material is simple to prepare and easy to recycle. It has excellent degradation effects on a variety of dyes and mixed dyes, and can be widely used in the routine treatment of organic pollutants in multiple scenarios.
[0025] (2) The piezoelectric self-Fenton composite film of the present invention can effectively enhance the piezoelectric catalytic activity, circumventing the limitations of the traditional Fenton process (high processing cost and environmental pH limitation), and providing a new technical means for the normalization of organic pollutant treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The degradation effects of different piezoelectric self-Fenton composite films on Rhodamine B;
[0028] Figure 2 The degradation effects of different piezoelectric self-Fenton composite films on methylene blue;
[0029] Figure 3 The degradation effects of different piezoelectric self-Fenton composite films on methyl orange;
[0030] Figure 4 Thermal diagram of UV curves of mixed dye degradation by different piezoelectric self-Fenton composite films;
[0031] Figure 5 The decolorization effect of different piezoelectric self-Fenton composite films on mixed dye degradation for 60 minutes;
[0032] Figure 6 The degradation effects of different films on Rhodamine B;
[0033] Figure 7The degradation effect of piezoelectric self-Fenton composite film on Rhodamine B under different pH degradation environments;
[0034] Figure 8 Comparison of the 30-min degradation effect of piezoelectric self-Fenton composite film on Rhodamine B under different pH degradation environments. DETAILED DESCRIPTION
[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0040] PVDF-HFP was purchased from Sigma-Aldrich, product number: 427187, density at 25°C was 1.78 g / mL.
[0041] Example 1
[0042] A method for preparing MgO@rGO@Fe3O4 / PVDF-HFP piezoelectric self-Fenton composite film:
[0043] (1) 0.5 g of PVDF-HFP particles were added to 5 ml of organic solvent (DMAC) and dissolved to obtain a polymer solution.
[0044] (2) Fe3O4, MgO and rGO (the amount of Fe3O4, MgO and rGO is 3% of the mass of the piezoelectric self-Fenton composite film) are added to 3 ml of DMAC, and treated with cell pulverization for 25 minutes (the cell pulverization treatment is ultrasonic pulverization; the power of ultrasonic pulverization is 97.5 W, the total time is 25 minutes, and the ultrasonic mode is on for 1.5 seconds and off for 2 seconds), and then added to the polymer solution prepared in step (1), mixed evenly, to obtain a mixed solution.
[0045] (3) The mixed solution was spread evenly in a 60 mm culture dish and deionized water was sprayed on the surface to obtain the MgO@rGO@Fe3O4 / PVDF-HFP piezoelectric self-Fenton composite film (denoted as 3% MgO@rGO@X / PVDF-HFP).
[0046] Example 2
[0047] Same as Example 1, except that Fe3O4 is replaced by Fe of equal mass.
[0048] Example 3
[0049] Same as Example 1, except that Fe3O4 is replaced by Fe2O3 of equal mass.
[0050] Example 4
[0051] Same as Example 1, except that Fe3O4 is replaced by FeS2 of equal mass.
[0052] Example 5
[0053] Same as Example 1, except that Fe3O4 is replaced by FePO4 of equal mass.
[0054] Example 6
[0055] Same as Example 1, except that Fe3O4 is replaced by FeC2O4 of equal mass.
[0056] Example 7
[0057] Same as Example 1, except that Fe3O4 is replaced by FePc of equal mass.
[0058] Example 8 (Blank)
[0059] The same as Example 1, except that Fe3O4 is not added in step (2), and the obtained film is MgO@rGO / PVDF-HFP.
[0060] Comparative Example 1
[0061] The same as Example 1, except that rGO is not added in step (2), and the obtained film is MgO@Fe3O4 / PVDF-HFP.
[0062] Comparative Example 2
[0063] The same as Example 1, except that MgO is not added in step (2), and the obtained film is rGO@Fe3O4 / PVDF-HFP.
[0064] Comparative Example 3
[0065] Preparation method of PVDF-HFP:
[0066] (1) 0.5 g of PVDF-HFP particles were added to 8 ml of organic solvent (DMAC) and dissolved to obtain a polymer solution.
[0067] (2) The polymer solution was spread evenly in a 60 mm culture dish and deionized water was sprayed on the surface to obtain a PVDF-HFP film (denoted as PVDF-HFP).
[0068] Effect Example 1
[0069] (1) Prepare 1×10 -5 mol / L Rhodamine B solution (simulated Rhodamine B wastewater, prepared with deionized water), 1×10 -5 mol / L methylene blue solution (simulated methylene blue wastewater, prepared with deionized water) or 1×10 - 5 mol / L methyl orange solution (simulating methyl orange wastewater, prepared with deionized water), take 10 ml in a beaker as the solution to be degraded. 50 mg of the piezoelectric self-Fenton composite film prepared in Examples 1 to 8 was placed in rhodamine B, methylene blue or methyl orange solution respectively. After dark adsorption for 2 hours, the piezoelectric self-Fenton degradation experiment was carried out under an ultrasonic power of 240 W. The degradation time was 30 minutes. During the degradation process, 4 ml of degradation liquid was taken every 5 minutes, and the absorbance of the degradation liquid sample was tested on an ultraviolet visible spectrophotometer (UV-2600). After the test, the degradation liquid sample was poured back into the beaker. Calculate the ratio of the absorbance at each time point in each group to the original absorbance (before degradation). The results are shown in Table 1. Figures 1 to 3 , Figure 1 The degradation effects of different piezoelectric self-Fenton composite films on Rhodamine B. Figure 2 The degradation effects of different piezoelectric self-Fenton composite films on methylene blue. Figure 3 The degradation effect of different piezoelectric self-Fenton composite films on methyl orange.
[0070] from Figures 1 to 3 It can be seen that the piezoelectric self-Fenton composite film prepared in the embodiment of the present invention shows good degradation efficiency for various organic pollutants.
[0071] Effect Example 2
[0072] (1) Prepare a mixed solution of rhodamine B, methylene blue, and methyl orange (using deionized water), with the concentration of each dye in the mixed dye being 1×10 -5 mol / L, the total concentration is 3×10 -5 mol / L, take 50ml into a beaker as the solution to be degraded.
[0073] 100 mg of the film (1-1, Blank) prepared in Example 8, the film (1-2, containing Fe) prepared in Example 2, the film (1-3, containing FeS2) prepared in Example 4, and the film (1-4, containing Fe3O4) prepared in Example 1 were placed in a mixed solution, and after dark adsorption for 2 hours, a piezoelectric self-Fenton degradation experiment was performed under an ultrasonic power of 240 W. The degradation time was 60 minutes. During the degradation process, 4 ml of degradation solution was taken every 5 minutes. The absorbance of the degradation solution sample was tested on an ultraviolet-visible spectrophotometer (UV-2600). After the test, the degradation solution sample was poured back into the beaker. The ratio of the absorbance at each time point of each group to the original absorbance (before degradation) was calculated.
[0074] 50 mg of the film prepared in Example 2 and 50 mg of the film prepared in Example 4 (two film compositions 2-1) were placed in a mixed solution, and after dark adsorption for 2 hours, a piezoelectric self-Fenton degradation experiment was performed under an ultrasonic power of 240 W. The degradation time was 60 minutes. During the degradation process, 4 ml of the degradation solution was taken every 5 minutes, and the absorbance of the degradation solution sample was tested on an ultraviolet-visible spectrophotometer (UV-2600). After the test, the degradation solution sample was poured back into the beaker. The ratio of the absorbance at each time point of each group to the original absorbance (before degradation) was calculated.
[0075] 50 mg of the film prepared in Example 2 and 50 mg of the film prepared in Example 1 (two film compositions 2-2) were placed in a mixed solution, and after dark adsorption for 2 h, a piezoelectric self-Fenton degradation experiment was performed under an ultrasonic power of 240 W. The degradation time was 60 min. During the degradation process, 4 ml of the degradation solution was taken every 5 min, and the absorbance of the degradation solution sample was tested on an ultraviolet-visible spectrophotometer (UV-2600). After the test, the degradation solution sample was poured back into the beaker. The ratio of the absorbance at each time point of each group to the original absorbance (before degradation) was calculated.
[0076] 50 mg of the film prepared in Example 4 and 50 mg of the film prepared in Example 1 (two film compositions 2-3) were placed in a mixed solution, and after dark adsorption for 2 h, a piezoelectric self-Fenton degradation experiment was performed under an ultrasonic power of 240 W. The degradation time was 60 min. During the degradation process, 4 ml of the degradation solution was taken every 5 min, and the absorbance of the degradation solution sample was tested on an ultraviolet-visible spectrophotometer (UV-2600). After the test, the degradation solution sample was poured back into the beaker. The ratio of the absorbance at each time point of each group to the original absorbance (before degradation) was calculated.
[0077] 25 mg of the film prepared in Example 8, 25 mg of the film prepared in Example 2, 25 mg of the film prepared in Example 4, and 25 mg of the film prepared in Example 1 (four film compositions 4-1) were placed in a mixed solution, and after dark adsorption for 2 hours, a piezoelectric self-Fenton degradation experiment was performed under an ultrasonic power of 240 W. The degradation time was 60 minutes. During the degradation process, 4 ml of the degradation solution was taken every 5 minutes, and the absorbance of the degradation solution sample was tested on an ultraviolet-visible spectrophotometer (UV-2600). After the test, the degradation solution sample was poured back into the beaker. The ratio of the absorbance at each time point of each group to the original absorbance (before degradation) was calculated.
[0078] Table 1 Grouping and dosage of films
[0079]
[0080] The results of the test are shown in Figure 4 and Figure 5 .
[0081] from Figure 4 and Figure 5 It can be seen that the MgO@rGO@Fe3O4 / PVDF-HFP piezoelectric self-Fenton composite film prepared in Example 1 has a good degradation effect on the components in the mixed dyes. This shows that the composite film doped with Fe3O4 as an iron source exhibits good redox activity in a variety of single dyes and mixed dye environments.
[0082] Effect Example 3
[0083] Prepare 1×10 -5mol / L Rhodamine B solution (simulating Rhodamine B wastewater, prepared with deionized water), take 10 ml in a beaker as the solution to be degraded. 50 mg of the film prepared in Example 1, Example 8 and Comparative Examples 1 to 3 were placed in the Rhodamine B solution respectively. After dark adsorption for 2 hours, a piezoelectric self-Fenton degradation experiment was carried out under an ultrasonic power of 240 W. The degradation time was 30 minutes. During the degradation process, 4 ml of degradation liquid was taken every 10 minutes, and the absorbance of the degradation liquid sample was tested on an ultraviolet visible spectrophotometer (UV-2600). After the test, the degradation liquid sample was poured back into the beaker. Calculate the ratio of the absorbance at each time point in each group to the original absorbance (before degradation). The results are shown in Table 1. Figure 6 .
[0084] Prepare 1×10 -5 mol / L Rhodamine B solution (simulating Rhodamine B wastewater, prepared with deionized water), take 10 ml in a beaker as the solution to be degraded. The solution to be degraded was subjected to a piezoelectric self-Fenton degradation experiment (denoted as US) under an ultrasonic power of 240W. The degradation time was 30 minutes. During the degradation process, 4 ml of degradation liquid was taken every 10 minutes, and the absorbance of the degradation liquid sample was tested on an ultraviolet visible spectrophotometer (UV-2600). After the test, the degradation liquid sample was poured back into the beaker. The ratio of the absorbance at each time point in each group to the original absorbance (before degradation) was calculated, and the results are shown in Figure 6 .
[0085] Effect Example 4
[0086] Prepare 1×10 -5 mol / L Rhodamine B solution (simulating Rhodamine B wastewater, prepared with deionized water), the initial solution pH is 7, take 10ml in a beaker as the solution to be degraded. Use HCl and NaOH to adjust the pH of the solution to be degraded to 3 and 11 respectively, to obtain solutions to be degraded with different pH. 50mg of the piezoelectric self-Fenton composite film prepared in Example 1 and Example 8 were placed in the above-mentioned solutions to be degraded with different pH values, respectively. After dark adsorption for 2h, the piezoelectric self-Fenton degradation experiment was carried out under the condition of ultrasonic power of 240W. The degradation time was 30min. During the degradation process, 4ml of degradation liquid was taken every 10min, and the absorbance of the degradation liquid sample was tested on an ultraviolet visible spectrophotometer (UV-2600). After the test, the degradation liquid sample was poured back into the beaker. Calculate the ratio of the absorbance at each time point of each group to the original absorbance (before degradation). The results are shown in Figure 7 The 30-min degradation rates of the samples in each group are compared. Figure 8 .
[0087] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a piezoelectric self-Fenton composite film, characterized in that: The following steps are involved: Add PVDF into an organic solvent and dissolve it to obtain a polymer solution; MgO and rGO are added into an organic solvent for cell crushing, and then the polymer solution is added and mixed evenly to obtain a mixed solution; The piezoelectric self-Fenton composite film is obtained by spreading the mixed solution.
2. The preparation method according to claim 1, characterized in that: It also includes adding iron at the same time as adding MgO and rGO.
3. The preparation method according to claim 2, characterized in that: The iron includes Fe, Fe2O3, Fe3O4, FeS2, FePO4, FeC2O4 or FePc.
4. The preparation method according to claim 2, characterized in that: The PVDF includes PVDF-HFP; The amount of iron, MgO and rGO used is 3% of the mass of the piezoelectric Self-Fenton composite film.
5. The preparation method according to claim 1, characterized in that: The cell pulverization treatment is ultrasonic pulverization treatment; the power of the ultrasonic pulverization treatment is 97.5W, the total time is 25 minutes, and the ultrasonic mode is on for 1.5 seconds and off for 2 seconds.
6. A piezoelectric self-Fenton composite film prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the piezoelectric self-Fenton composite film according to claim 6 in degrading organic pollutants.
8. The use according to claim 7, characterized in that: The organic pollutants include one or more of rhodamine B, methylene blue and methyl orange.
9. A method for degrading organic pollutants by piezoelectric self-Fenton, characterized in that: The following steps are involved: The piezoelectric self-Fenton composite film according to claim 6 is immersed in a solution of organic pollutants, and after dark adsorption, a piezoelectric self-Fenton degradation reaction is carried out under the action of ultrasound.
Citation Information
Patent Citations
Catalytic degradation method for dye-containing wastewater and catalyst thereof
CN109650521A
Metal reducing-electrofenton system and application thereof
CN109896599A
Preparation method of high specific surface area graphene-metal oxide composite sponge
CN110240731A
Antibacterial film with PVDF-HFP (Polyvinylidene Fluoride-Hexafluoropropylene) as substrate and blended nanofiller as well as preparation method and application of antibacterial film
CN114410039A
Cited By
Piezoelectric catalysis-Fenton self-coupling stage treatment underground water equipment
CN120987455A